Lateral skull base approaches in the management of benign parapharyngeal space tumors. Issue 3 (June 2015) - Prasad, Sampath Chandra; Piccirillo, Enrico; Chovanec, Martin; La Melia, Claudio; De Donato, Giuseppe; Sanna, Mario
Abstract Objective To evaluate the role of lateral skull base approaches in the management of benign parapharyngeal space tumors and to propose an algorithm for their surgical approach. Methods Retrospective study of patients with benign parapharyngeal space tumors. The clinical features, radiology and preoperative management of skull base neurovasculature, the surgical approaches and overall results were recorded. Results 46 patients presented with 48 tumors. 12 were prestyloid and 36 poststyloid. 19 (39.6%) tumors were paragangliomas, 15 (31.25%) were schwannomas and 11 (23%) were pleomorphic adenomas. Preoperative embolization was performed in 19, stenting of the internal carotid artery in 4 and permanent balloon occlusion in 2 patients. 19 tumors were approached by the transcervical, 13 by transcervical–transparotid, 5 by transcervical–transmastoid, 6, 1 and 2 tumors by the infratemporal fossa approach types A, B and D, respectively. Total radical tumor removal was achieved in 46 (96%) of the cases. Conclusion Lateral skull base approaches have an advantage over other approaches in the management of benign tumors of the parapharyngeal space due to the fact that they provide excellent exposure with less morbidity. The use of microscope combined with bipolar cautery reduces morbidity. Stenting of internal carotid artery gives a chance for complete tumor removal with arterial preservation.